Systemic sclerosis: state of the art on clinical practice guidelines. (18th October 2018) - Smith, Vanessa; Scirè, Carlo Alberto; Talarico, Rosaria; Airo, Paolo; Alexander, Tobias; Allanore, Yannick; Bruni, Cosimo; Codullo, Veronica; Dalm, Virgil; De Vries-Bouwstra, Jeska; Della Rossa, Alessandra; Distler, Oliver; et al.
Abstract : Systemic sclerosis (SSc) is an orphan disease characterised by autoimmunity, fibrosis of the skin and internal organs, and vasculopathy. SSc may be associated with high morbidity and mortality. In this narrative review we summarise the results of a systematic literature research, which was performed as part of the European Reference Network on Rare and Complex Connective Tissue and Musculoskeletal Diseases project, aimed at evaluating existing clinical practice guidelines or recommendations. Only in the domains 'Vascular & Ulcers' (ie, non-pharmacological approach to digital ulcer), 'PAH' (ie, screening and treatment), 'Treatment' and 'Juveniles' (ie, evaluation of juveniles with Raynaud's phenomenon) evidence-based and consensus-based guidelines could be included. Hence there is a preponderance of unmet needs in SSc referring to the diagnosis and (non-)pharmacological treatment of several SSc-specific complications. Patients with SSc experience significant uncertainty concerning SSc-related taxonomy, management (both pharmacological and non-pharmacological) and education. Day-to-day impact of the disease (loss of self-esteem, fatigue, sexual dysfunction, and occupational, nutritional and relational problems) is underestimated and needs evaluation.